Anti-Inflammatory and Antinociceptive Effects of Salbutamol on Acute and Chronic Models of Inflammation in Rats: Involvement of an Antioxidant Mechanism. (14th May 2012) - Uzkeser, Hulya; Cadirci, Elif; Halici, Zekai; Odabasoglu, Fehmi; Polat, Beyzagul; Yuksel, Tugba Nurcan; Ozaltin, Seda; Atalay, Fadime
Abstract : The possible role of β -2 adrenergic receptors in modulation of inflammatory and nociceptive conditions suggests that the β -2 adrenergic receptor agonist, salbutamol, may have beneficial anti-inflammatory and analgesic effects. Therefore, in this study, we induced inflammatory and nociceptive responses with carrageenan-induced paw edema or cotton-pellet-induced granuloma models, both of which result in oxidative stress. We hypothesized that salbutamol would prevent inflammatory and nociceptive responses by stimulating β -2 adrenergic receptors and the prevention of generation of ROS during the acute inflammation process in rats. Both doses of salbutamol used in the study (1 and 2 mg/kg) effectively blocked the acute inflammation and inflammatory nociception induced by carrageenan. In the cotton-pellet-induced granuloma test, both doses of salbutamol also significantly decreased the weight of granuloma tissue on the cotton pellets when compared to the control. Anti-inflammatory and analgesic effects of salbutamol were found to be comparable with those of indomethacin. Salbutamol decreased myeloperoxidase (MPO) activity and lipid peroxidation (LPO) level and increased the activity of superoxide dismutase (SOD) and level of glutathione (GSH) during the acute phase of inflammation. In conclusion, salbutamol can decrease acute and chronic inflammation, possibly through the stimulation of β -2 adrenergic receptors. This anti-inflammatory effect may be of significance in asthma treatment, where inflammation also takes part in the etiopathology. This study reveals that salbutamol has significant antioxidative effects, which at least partially explain its anti-inflammatory capabilities. These findings presented here may also shed light on the roles of β -2 adrenergic receptors in inflammatory and hyperalgesic conditions.